Uma análise da integração curricular no IFS/Campus Aracaju : sua constituição e os seus efeitos sobre o ensino de matemática no curso de eletrotécnica - Nascimento, Shirleyde Dias do (2017)
This present dissertation, submitted to Programa de Pós graduação em ensino de ciências e matemática da Universidade Federal de Sergipe (UFS), performed a study about the integrated curriculum, focusing on analyze its composition and how to know the effective process of learning math, comprehending the composition of this process to this specific grade, having as a base the Nível Técnico and the Nível Médio of the electronic course, of the Instituto Federal de Educação, Ciência e Tecnologia de Sergipe – IFS/Campus Aracaju/SE. The organization of the Integrated Curriculum comes from Decree nº 5.154 / 2004. From that, other forms of medium-level professional education was consolidated, including the possibility of the technical teaching way to be offered as an integrated form to the middle school level.In order for the central objective of this research happened, were requested some registration data: document analysis, in order to be able to know how the Integrated Curriculum is organized, examining whether the Pedagogical Project Course of the Nível Técnico and the Nível Médio of the electronic course directs towards the integration Between the different areas of knowledge and identify how mathematical contents are contemplated; We performed semi-structured interview with teachers, but also with the students to evaluate the design of Integrated Curriculum and focus groups with students to identify about the relevance of mathematical subjects to technical training and the meaning attributed to that knowledge. Regarding the document analysis, it shows us how to integrate different kinds of acknowledge ways, not only, affirming that the concretization of the integrated curricular should be a methodology priority appropriating to the school subjects, although the evidence of the purpose could not be shown, by the display of the pedagogical practice of the teachers. It was seized in the speech of teachers and students, conceptions about the Integrated Curriculum clearing pointing out a reference to the course offered which integrates the technical education to the form to the middle school level with school subjects working out with different objectives, in one way the general subjects prepares for the Exame Nacional do Ensino Médio -ENEM, in other hand, it deals with the technique to join the market business. The students noticed the lack of the linking between the school subjects showing out that the math contents effectively turn to the form to the middle school level, and not involving the technical school subjects, demonstrating that the not composable situations between in teacher’s methodology ways affect the learning process of math. In summary, it was concluded by the provided elements that the way of the integrated curriculum is formed, by the lack of the linking of the school subjects in this pedagogical curriculum, don't have significant effect on the process of learning math.